#TITLE_ALTERNATIVE# - WINDHARTO NIM: 21816009, AGUS
The inventory plays an important role for company business, because most of the working capital will be absorbed in the inventory value, which will burden the financial cash flow of the company. The inventory has to be managed at the optimum level, to make balance between the service level and the inventory level. This research gives an alternative method for calculation of safety stock that correlates the value factors and the risk factors of starting materials. The retrospective data at 2017 is collected for 550 items of raw materials and 725 items of packaging materials. The value factor is calculated using ABC analysis, while the risk factor is calculated using some parameters (supplier audit, percentage of rejection and complaint, delay of delivery, and function of starting materials). Then, the value and the risk factors are combined for determination of the value-risk score (VR score) used for safety stock calculation. The comparison study of amount and value of safety stock is compared with the current method in company A and the Z score method. The result of the research showed that the VR score method can reduce the inventory value of raw materials by 34% compared with the current method in company A. The VR score method for the packaging materials recommends to raise 50% of safety stock compare with the current method, but still lower than safety stock calculation using the Z score method. This is because in company A, the risk score of packaging materials is higher than raw materials, so packaging materials require higher safety stock level.